2020
DOI: 10.15294/jbat.v9i1.24935
|View full text |Cite
|
Sign up to set email alerts
|

Clove Oil Extraction by Steam Distillation and Utilization of Clove Buds Waste as Potential Candidate for Eco-Friendly Packaging

Abstract: As a tropical country which has abundant of spices, Indonesia is challenged to increase the economic values of spices commodity in raw material form (wet or dry). One way to raise the economic values of these commodities is by modifying into its derivatives. Clove is one of spices commodity which can be processed furthermore into an essential oil. By transforming clove from raw material to essential oil, the economic value increases from 2 to 20 times per kilogram.  In this present research, the extraction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…The compounds that were not present in the research results were probably caused by clove bud samples from cigarette factory waste, namely clove flower dust so that the samples used were less controlled. The number of compounds obtained is in line with the research of Ratri et al (2020) [6], however, α-ylangene and methyl salicylate compounds were not found in the study. Based on this, quality information of clove oil can be important information in improving the quality of local CBO products, so the product has a high selling value and is a real step in utilizing cigarette factory waste in Indonesia.…”
Section: Counting Eugenol Levels Of Cbosupporting
confidence: 87%
See 1 more Smart Citation
“…The compounds that were not present in the research results were probably caused by clove bud samples from cigarette factory waste, namely clove flower dust so that the samples used were less controlled. The number of compounds obtained is in line with the research of Ratri et al (2020) [6], however, α-ylangene and methyl salicylate compounds were not found in the study. Based on this, quality information of clove oil can be important information in improving the quality of local CBO products, so the product has a high selling value and is a real step in utilizing cigarette factory waste in Indonesia.…”
Section: Counting Eugenol Levels Of Cbosupporting
confidence: 87%
“…The commonly used parts of cloves are buds and leaves and the oil is used for the food, medicinal, cosmetic, and agricultural industries, such as antimicrobial agents, antivirals, analgesics, insecticides, larvicides, ant repellent Solenopsis invicta, and it is used to improve memory deficits due to oxidative stress [4]. The study of Batiha et al (2020) [5] reported that the result of GC-MS shown that clove oil contained 36 compounds, including eugenol, β-caryophyllene, eugenylacetate, ethyl hexanoate, 2-heptanone, α-humulene, calacorene, humulenol, and calamen-ene while Ratri et al (2020) [6] reported that steam distillation clove bud oil (CBO) from fresh bud clove contained 8 compounds, namely methyl salicylate, chavicol, eugenol, α-ylangene, caryophyllene, humulene, eugenyl acetate, and caryophyllene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Boiling water produces steam, and that steam carries the volatile oils with it. The oil and water are then separated by cooling and humidification ( 46 ).…”
Section: Extraction Methods Of Clove Essential Oilmentioning
confidence: 99%
“…It is higher than the strength of Styrofoam, paper, and films but much lower than other RF dedicated substrates (such as RO4003 and FR4). For instance, the tensile strength of corrugated boards can reach up to 3.3 MPa for an elongation of 6% [17]. This value is high when compared with other materials such as Styrofoam (0.4 MPa), paper (0.32 MPa) but much lower than that of FR4 substrate (430 MPa) [18,19].…”
Section: Cardboard Characterizationmentioning
confidence: 97%